Access to an improved water source and its measurement: the case of Misiones (Argentina) - González, Fernando Antonio Ignacio (2019)
This aim of this work is to analyze the situation of the Province of Misiones (Argentina) interms of the access to improved water of its inhabitants, while discussing different existingtheoretical proposals to quantify the phenomenon. Data from the Permanent HouseholdSurvey, Annual Survey of Urban Households, National Household Expenditure Survey andResearch Project on Contemporary Argentine Society are used. It is observed that Misioneshas a higher percentage of people who do not have access to an improved water source,between 2011-2018. Worst indicators are also observed in terms of affordability, even thoughthere are no significant differences in quality of supply. High levels of inequality are observedamong those who manage to access improved water and those who do not.